MO830COVID-19 INFECTION IN HEMODIALYSIS POPULATION. (29th May 2021) - AlSahow, Ali; AlQallaf, Ahmed; Bahbahani, Hamad; Alyousef, Anas; Bahbahani, Yousif; Alhelal, Bassam; AlRajab, Heba; Almuhaiteeb, Abdullah; Shalaby, Heba; Elabbadi, Mohamed; Elsebaei, Mohammad; Abdallah, Emad; et al.
Abstract: Background and Aims: A third novel coronavirus leading to severe respiratory infection (coronavirus disease 2019, COVID-19) was first identified in Wuhan, China in December 2019; 1 as of January 2021, more than 90 million person infected and more than 2, 000, 000 died worldwide. 2 Hemodialysis (HD) patients are at risk of COVID-19 infection but reported infection rates are variable. 1 We report results of prospectively collected data on HD patients who contracted COVID-19 infection in Kuwait. Method: Demographics, comorbidities, and mortality data for HD patients who got infected with COVID-19 in Kuwait from 1/March/2020 to 31/July/2020 were collected and analyzed. Results: Kuwait population during that same period was 4, 600, 000 (63% Males and 37%Females). 3 Total number of HD patients was 2000 (representing only 0.04% of the total population with 52% Males and 48% Females). Total number of COVID-19 cases confirmed by PCR from nasopharyngeal swab was 66, 957. Total number of infected HD patients was 141 (representing 7% of the total HD population and 0.2% of the total number of people infected with COVID-19 in Kuwait). All COVID-19 positive cases were treated for free in ministry of health hospitals Mean age for HD patients with COVID-19 was 57 (54 for males and 62 for males). DM was present in 70%, HTN in 95%, CV disease in 61%, respiratory illness in 20.5%, and ICU admission was required for 31 patients (22%), with 80% requiring intubation and assisted ventilation. Conventional HD was switched to CRRT in 61 patients (43%). Steroids were used for 23%, convalescent plasma in 1 patient, lopinavir/ritonavir in 7 patients, tocilizumab in 3 patients. Total number of mortality due to covid-19 infection in Kuwait was 447 (0.7% of the total cases). 4 Total mortality in HD population during that period for any reason was 100 (5% of the total HD population), however, total mortality due to COVID-19 infection was 30% of the total mortality in the HD population (and 7% of the total COVID-19 related mortality in the country). Patients who died were older with mean age of 63 vs 56 for survivors and had respiratory illness more frequently (27% vs 18%) and 60% were males. Of those who were switched to CRRT, 21 of 61 (34%) died. Of the 31 HD patients admitted to ICU, 19 (61%) died. Conclusion: Despite the fact the HD population represents only a small fraction of the total population, they represent a sizable proportion of the total COVID-19 positive cases and a significant percentage of the total COVID-19 related mortality. This study highlights the increased susceptibility of HD population to COVID-19 infection, which is associated with high rate of mortality, although lower than mortality rates reported in Europe and the united states. 5, 6